2020
DOI: 10.1016/j.ijid.2020.09.264
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing pattern in primary care practice in Federal Territory Kuala Lumpur and Putrajaya

Abstract: studies from developed countries and countries in this region. It is imperative that these results be shared with relevant stakeholders and a multimodal strategy is developed to improve these rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Our study findings have useful implications for clinical practice in primary care settings. First, the use of empirical antibiotics in a high proportion (90%) of patients diagnosed with uncomplicated UTI at the KBPFMD is similar to studies from other LMICs [22,23,39]. This use of empirical antibiotics is justifiable as they are effective and form the mainstay of treatment in facilities with poor access to free CDST services [6,7].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Our study findings have useful implications for clinical practice in primary care settings. First, the use of empirical antibiotics in a high proportion (90%) of patients diagnosed with uncomplicated UTI at the KBPFMD is similar to studies from other LMICs [22,23,39]. This use of empirical antibiotics is justifiable as they are effective and form the mainstay of treatment in facilities with poor access to free CDST services [6,7].…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies reported poor knowledge about STGs among physicians in primary care settings and non-availability of the recommended drugs as primary reasons for low adherence in choosing the right antibiotic [22,23,39,41]. In contrast, treating physicians at KBPFMD are exposed to STGs during teaching-learning activities for postgraduate students (residents), as it is a satellite center of a teaching hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation